Developmental and reproductive toxic effects of exposure to microplastics: A review of associated signaling pathways - Dubey, Itishree; Khan, Sabbir; Kushwaha, Sapana (Frontiers in Toxicology, 2022)
Microplastics (MPs), small pieces of plastic (∼5 mm), are released into the environment not only as a result of the decomposition of large-sized plastics but also from day-to-day use of plastic products. Chronic exposure to MPs has been attributed to harmful effects on aquatic organisms and rodents. Effects include gastrointestinal toxicity, hepatotoxicity, neurotoxicity, and reproductive and developmental toxicities. Exposure to MPs may also potentially affect human health. Herein, we reviewed the impact of MPs on male and female reproductive systems and the associated mechanisms involved in the reproductive and developmental toxicities of MPs. We performed a literature search in Google Scholar and PubMed using the following keywords: MPs and reproductive toxicity; MPs and developmental studies; MPs and infertility; MPs and aquatics; and MPs and rodents. Evidence of MPs accumulation has been reported in many organs of humans and experimental models. The harmful effects of MPs have been manifested in male and female reproductive systems of mammalian and aquatic animals, including developmental effects on gametes, embryos, and their offspring. This review describes various signaling pathways involved in MPs-associated male and female reproductive and developmental toxicities.